Seasonal microbial profiling of left kidney and stomach of farmed adult greenlip abalone (Haliotis laevigata). (17th December 2020) - Wang, Yanhui; Pyecroft, Stephen; Barton, Mary
Abstract: As sequencing and data analysis methods improve and more bacterial species are identified, microbial profiling has been performed more widely in marine species. To enable the development of potential prophylactic strategies against bacterial disease in abalone induced by elevated water temperatures, the left kidney and stomach samples of six unaffected adult greenlip abalone Haliotis laevigata were sampled in summer and winter to enable comparisons of endogenous abalone microbial profiles. Under the experimental conditions, needle aspiration of selected tissues did not allow collection of adequate amounts of abalone tissue for microbiome studies. Tenericutes, Proteobacteria and Fusobacteria were the three major phyla present in most samples which were previously identified in other marine species. Propionibacterium, Psychrilyobacter, Pseudoruegeria, Ruegeria, Arcobacter, Shewanella, Pseudoalteromonas, Streptococcus and Mycoplasma were the nine genera that were detected in 0.5% or more of all samples. The beta‐diversity results indicated there were significant differences between summer and winter samples. The microbiome structures were different between left kidney and stomach samples. It was found that the abalone left kidney harboured diverse bacteria and was a potential indicator of the physiological status of the abalone, offering an alternative site for microbial profiling of abalone, apart from the gastrointestinal tract.